Centris aenea (Hymenoptera, Apidae): a Ground-nesting Bee with High Pollination Efficiency in Malpighia emarginata DC (Malpighiaceae) - Geane Almeida Oliveira (Universidade Estadual de Feira de Santana, 2013)
This study aimed to assess the efficiency of Centris aenea Lepeletier as pollinator of Malpighia emarginata DC. The pollination efficiency was determined according to three criteria: 1) the pollen deposition rate of M. emarginata and other plant species on the thorax ventral region of females, 2) the rate of M. emarginata fruit set after a single visit, and 3) the pollen deposition rate on the stigma after one single visit. 59% of the pollen grains deposited on the ventral region of C. aenea came from flowers of M. emarginata. The fruit set after a single visit by C. aenea (21%) was much higher than that reported previously for Centris tarsata Smith. We argue that pollination efficiency of C. aenea can be related to its body size, since that females of C. aenea can carry larger amounts of pollen grains of M. emarginata than C. tarsata, as well females of C. aenea are able to touch a larger stigma area, resulting in higher fruit sets after a single visit. Our study suggests that only one visit by C. aenea ensures fruit set in M. emarginata.